Integrated pest management in the landscape - Clokey, Joe; Harrigan, Jim; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
See how to integrate biological, cultural, physical, horticultural and chemical strategies into an effective pest management program. Explore how the basic IPM strategies are effectively applied in various landscape situations and how an individualized IPM program can be set up. Then visit various settings where IPM is used, including home gardens, Disneyworld's Epcott Center and San Francisco's Conservatory of Flowers
Title from title screen
Also published on VHS in 1988
DVD format
Keywords: Landscape gardening; Garden pests -- Integrated control; Agricultural pests -- Biological control; Biological pest control agents; Garden pests -- Control; Pests -- Integrated control